EVALUASI USER INTERFACE PADA APLIKASI PACITAN TOURISM - Candra Budi Susila (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
"Evaluation of Applications User Interface In Pacitan Tourism" is a study with the aim of analyzing and evaluating the user interface on Tourism Pacitan applications that are expected to facilitate the users in their use. Applications Pacitan Tourism is an application developed by the Department of Tourism Pacitan useful for tourists to obtain information related to tourist spots in Pacitan. The evaluation method used is the method Eight Golden Rules whereby the use of 8 rules or 8 rules in designing a user interface which include consistency, allowing users to use the shortcut, providing feedback informative, dialogue has a certain scope, provides error handling is simple, easily return to a previous action, supporting the internal control center, reducing the burden of short-term memory. The results of this study are obtained variable consistency, use shortcuts, and dialogue has a certain scope can be said to be unfavorable recommendation given to the application developer is a prototype that will be used as a reference for developers of applications Pacitan Tourism in developing the user interface on the application requires a change design to the application of interest to the user. Keyword: Evaluation, Pacitan Tourism, Travel, Eight Golden Rules Of Design.